Topographical and Geodesic Information System - Santos Rodríguez, Ricardo (2009)
In the projects of geodesic and topographical engineering, precise mathematical calculations are carried out in a fast way and economic to apply it to the designs of the works of engineering, so much in the urban and rural space. Because of it the development of the Geodesic and topographical Information System called program present (SisTopGeo), is going to permit us to execute several of the very useful applications and of common use in Topography, Geodesy and basic Astronomy, permitting iterative immediate results, the ones that will be obtained entering the data of field and with only pressure the button calculation, the dependable results will be obtained, the same that will permit immediately to be represented in a plan A they determined extension of land, through existing programs of drawing as Autocad Land, Civil CAD, among others. With the data and results obtained applied to the systems SisTopGeo, Progrageod (IGN), CoordTrans (Franson Tecnology) and Geocalc (Blue Marble Geographics), was done the satisfactory comparisons being obtained results and being found that the SisTopGeo throws dependable results. Such it is so upon doing the Geographical Coordinates transformation comparisons to UTM processed by the four systems is found that the maximum variation to the east is of -2.806mm for the Station Pilán (1er Order) and in the north the maximum variation is of 8.458mm for the Station Banco Hipotecario; all compared with the system SisTopGeo. In the comparisons with the IGN, is found that the maximum variation to the east is -2.80mm that corresponds to the Station Pilán (1er Order) and for the north the maximum variation is -8.358mm for the Station Banco Hipotecario. With the two comparisons is observed that in the axis of the abscissas (This) has a maximum variation of -2.8mm and in the axis of the orderly (North) said variation is of ±8.4mm, for leading Stations; for which can be concluded that the results found by the SisTopGeo are applicable to our reality.